MsTHI1 overexpression improves drought tolerance in transgenic alfalfa (Medicago sativa L.) - Yin, Hang; Wang, Zhaoyu; Li, Han; Zhang, Yu; Yang, Mei; Cui, Guowen; Zhang, Pan (Frontiers in Plant Science, 2022)
Drought stress caused by global warming in recent years has become a major constraint on agriculture. The thiamine thiazole synthase (THI1) is responsible for controlling thiamine production in plants and displaying a response to various abiotic stresses. Nonetheless, most THI1 activities in plants remain largely unknown. In this study, we extracted MsTHI1 from alfalfa and demonstrated its beneficial impact on improving plant's resistance to stress conditions. The highest levels of MsTHI1 expression were identified in alfalfa leaves, triggered by exposure to cold, drought, salt, or alkaline conditions. MsTHI1 upregulation in drought-stressed transgenic plants resulted in enhanced accumulation of vitamin B1 (VB1), chlorophyll a (Chl a), chlorophyll b (Chl b) and soluble protein, higher SPAD value, and the activity of POD, maintained Fv/Fm, as well as decreased lipid peroxidation. Moreover, overexpression of MsTHI1 up-regulated the transcription of THI4, TPK1, RbcX2, Cu/Zn-SOD, CPK13, and CPK32, and down-regulated the transcription of TH1 and CPK17 in transgenic alfalfa under drought stress. These results suggested that MsTHI1 enhances drought tolerance by strengthening photosynthesis, regulating the antioxidant defense system, maintaining osmotic homeostasis, and mediating plant signal transduction.